2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34458
|View full text |Cite
|
Sign up to set email alerts
|

Development of Employability Skills in Engineering Disciplines through Co-op

Abstract: is a Mechanical Engineering undergraduate student from York University, class of 2020. She has worked on engineering co-op education research projects since September 2018 and presented her first paper at a conference in June 2019. She is passionate about understanding the co-op education system, to provide the best experience for students. She is also very involved in her school community and works with students and faculty alike to improve community engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In prior research, we highlighted the impact of skill preparation before co-op on the ease of adapting in a new work environment [13]. We found that there was a discrepancy between students in different engineering discipline in how developed their employability skills were.…”
Section: Background Literaturementioning
confidence: 87%
“…In prior research, we highlighted the impact of skill preparation before co-op on the ease of adapting in a new work environment [13]. We found that there was a discrepancy between students in different engineering discipline in how developed their employability skills were.…”
Section: Background Literaturementioning
confidence: 87%